Subnuclear organization of parabrachial efferents to the thalamus, amygdala and lateral hypothalamus in C57BL/6J mice: a quantitative retrograde double labeling study - Tokita, Kenichi (2010)
The present study investigated the subnuclear organization of collateralized efferent projection patterns from the mouse parabrachial nucleus (PbN), the second taste relay in rodents, to higher gustatory centers, including the ventroposteromedial nucleus of the thalamus (VPMpc), central nucleus of the amygdala (CeA) and lateral hypothalamus (LH). We made injections of the retrograde tracer red and green latex microspheres into the VMPpc and CeA (VPMpc-CeA group), VMPpc and LH (VPMpc-LH group) or CeA and LH (CeA-LH group, n = 6 for each group). Injections into these areas preferentially resulted in retrograde labeling in the ipsilateral PbN in all groups. Cells projecting to the VPMpc, CeA, and LH were generally found in all subnuclei, but were differentially distributed. VPMpc-projecting cells predominated in gustatory-related subnuclei, CeA-projecting neurons predominated in the external lateral (el) subnucleus, and concentrated labeling was observed in the dorsal lateral subnucleus (dl) following LH injection. Double-labeled neurons were found for all groups, almost entirely ipsilaterally and primarily in the medial (m), waist area (wa), ventral lateral (vl) and el subnuclei. These results suggest that PbN neurons in different subdivisions have different projection and collateralization patterns to the VPMpc, CeA and LH. Functional implications of these projections are discussed with an emphasis on their roles in taste.